Perlindungan Hukum Terhadap Keamanan Data Pribadi Nasabah - Fahmi, Khairil; Akbar, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Digital world players in various corners of the world need what is called electronic space for their activities. One of the very rapid developments today is the development in the field of information technology, which is applied in the banking world, including internet banking. Internet Banking is no longer a foreign term for the Indonesian people, this is due to the many national banks that use internet banking services, the internet or what is also called Cyberspace, can actually be interpreted as a space for electronic entities (netters) to interact. Internet banking allows customers to make payments online. Internet banking also provides accommodation for banking activities through computer networks anytime and anywhere quickly, easily and safely because it is supported by a strong security system. This is useful for ensuring the security and confidentiality of data and transactions made by customers. In addition, with internet banking, banks can increase the speed of service and reach in banking activities. In the development of banking technology such as internet banking, banks must pay attention to aspects of customer protection, especially security related to customer privacy. Misuse of privacy data or personal data of a person on the internet is mostly directed towards commercial matters, but it does not rule out the possibility of misuse of a person's personal data being aimed at other things that are detrimental